Synthesis of antitumor 3, 4, 6, 7-tetrahydro-2H-pyrimido[1, 6-c]quinazolin-2-imine derivatives via reductive dearomatization-initiated intramolecular cyclization. Issue 23 (9th June 2016) - Li, Wei; Zhou, Xiaotian; Chen, Yang; Guo, Shunmin; Ba, Feifei; Tian, Wei; Yang, Chao; Wang, Mingping; Liu, Yu; Song, Yunlong; Zhu, Ju; Zhou, Youjun; et al.
Abstract: In light of the importance of N -fused heterocycles in pharmaceuticals, there is continuing interest in research on N -fused heterocycles and their preparation. A new and efficient reductive dearomatization-initiated intramolecular cyclization reaction with a broad scope has been developed, affording 3, 4, 6, 7-tetrahydro-2 H -pyrimido[1, 6- c ]quinazolin-2-imine derivatives. Notably, this type of compound showed good inhibitory activity against specific kinases and human cancer cell lines. These results might mean a new molecular scaffold for the development of new antitumor agents. Graphical abstract: